Sentence vs. Word Perception by Young Healthy Females: Toward a Better Understanding of Emotion in Spoken Language - Sinvani, Rachel-Tzofia; Sapir, Shimon (Frontiers in Global Women's Health, 2022)
Expression and perception of emotions by voice are fundamental for basic mental health stability. Since different languages interpret results differently, studies should be guided by the relationship between speech complexity and emotional perception. The aim of our study was therefore to analyze the efficiency of speech stimuli, word vs. sentence, as it relates to the accuracy of four different categories of emotions: anger, sadness, happiness, and neutrality. To this end, a total of 2235 audio clips were presented to 49 females, native Hebrew speakers, aged 20-30 years (M= 23.7; SD=2.13). Participants were asked to judge audio utterances according to one of four emotional categories: anger, sadness, happiness, and neutrality. Simulated voice samples were consisting of words and meaningful sentences, provided by 15 healthy young females Hebrew native speakers. Generally, word vs. sentence was not originally accepted as a means of emotional recognition of voice; However, introducing a variety of speech utterances revealed a different perception. Thus, the emotional conveyance provided new, even higher precision to our findings: Anger emotions produced a higher impact to the single word (2 = 10.21, p<0.01) as opposed to the sentence, while sadness was identified more accurately with a sentence (2 = 3.83, p=0.05). Our findings resulted in a better understanding of how speech types can interpret perception, as a part of mental health.